Help-seeking attitudes and behaviors in adolescents with mental health problems - Lustig, Sophia (2022)
Many children and adolescents are affected by mental health problems. At the same time, a significant proportion of these young people do not receive professional help. One reason for this treatment gap is the low help-seeking behavior among adolescents. This is a serious problem, as a lack of professional support as well as delayed treatment onset in this phase of life can lead to chronicity and worsening of mental health issues. The aim of the present work is therefore to better understand the help-seeking process of adolescents with mental health problems and to improve the utilization of professional support. To this end, a theoretical framework is developed to represent the help-seeking process of adolescents with mental health problems in an integrative socio-cognitive model. In addition, four scientific studies are presented, examining help-seeking attitudes and behaviors and introducing interventions designed to improve help-seeking behavior for adolescents with mental health problems. Study 1 evaluates an intervention program from the school-based SEYLE study ('Saving and Empowering Young Lives in Europe'), which was designed to promote help-seeking behavior and mental health among adolescents. It was found that only few students took advantage of the support offered, demonstrating no overall effect of the intervention program. However, among those participants who actively used the program, increased utilization of professional support was evident at the 1-year follow-up. Study 2 presents another school-based project designed to promote help-seeking behavior among adolescents. The ProHEAD study ('Promoting Help-seeking using E-technology for ADolescents') has been implemented in schools across Germany since 2018 and aims to support mental health, prevent the manifestation of mental disorders and to promote help-seeking for mental health problems in adolescents. Following a school-based screening, students in need are invited to an online intervention that offers them individually tailored help in seeking professional support. Study 3 evaluates preliminary data from the ProHEAD project collected during the first wave of the COVID-19 pandemic in 2020. Compared to a pre-lockdown sample, youth in the first lockdown reported more positive help-seeking attitudes for mental health problems. Study 4 examines the average time it took youth with suicidal thoughts and behaviors to seek professional support after their mental health problems first emerged. It was found that the average help-seeking delay was 12 to 24 months and that the delay was particularly long for those with a higher symptom burden.
Keywords: Hochschulschrift